VARIABEL PRODUKSI CAMEL DAN KARAKTERISTIK BANK LAINNYA UNTNUK MEMPREDIKSI KEBANGKRUTAN BANK DI INDONESIA - Januarti, Indira (JURNAL BISNIS STRATEGI, 2002)
The objectives of this study to provide an empirical evidence variablesproxy for CAMEL and other bank characteristics for predicting bank bankcruptcy . The study uses 333 bank as sample which comprise of governmental bank, general bank and regional development bank in Indonesia tor one and two years before bankcrupt.The hypothesis was analysed using univariate and multivariate logistic regression. The result shows that variables equity, loanta, NIM, ROA, Core, Insider and Logsize were significantly different between bankcruptbank and non-bankcrupt bank. The accurancy of model for predicting 199 7bankcruptcy to 1999 bankcruptcy tend to decrease.Â